The distribution of unlevered housing in American urban areas. Issue 5 (14th May 2018) - Lijing, Du; Huang, Jian; Singer, Daniel; Torna, Gokhan
Abstract : Purpose: The purpose of this paper is to investigate the impact of social and economic factors on home ownership as an investment in American urban areas. Design/methodology/approach: The authors run a spatial analysis using home ownership data on 817 American counties from US Census Bureau's 2013 American Community Survey. Findings: While the amenity value of home ownership is found to be important to overall housing tenure decisions, it is found to be less so for the ownership cohort without mortgages. Economic factors are found to impact the spatial pattern of owner-occupied housing without mortgage differently than that of all owner-occupied housing. The implications of these differences for investors are explored. Research limitations/implications: The results may lack generalizability outside of the American urban areas. Practical implications: As a result of the findings of this study, a shift in investor focus from minimizing initial housing costs to sustainable housing costs is recommended. Originality/value: This study provides insights into the social and economic dimensions of owner-occupied housing in order to create a more profitable investing policy for promoting home ownership.